Case report: Fatal poisoning caused by additive effects of two barbiturates - Takei, Sella; Kinoshita, Hiroshi; Jamal, Mostofa; Kumihashi, Mitsuru; Yamashita, Tadayoshi; Tanaka, Etsuko; Kawahara, Sachiko; Abe, Hiroko; Tsutsui, Kunihiko; Kimura, Shoji (Frontiers in Pharmacology, 2023)
A case of fatal poisoning involving multiple psychotropic drugs is presented. Quantitative toxicological analysis showed femoral blood concentrations of pentobarbital, phenobarbital, duloxetine, acetaminophen and tramadol were 10.39, 22.57, 0.22, 0.61 and 0.22 μg/ml, respectively. We concluded that the death was due to the additive effects of two barbiturates. As both pentobarbital and phenobarbital act on gamma-aminobutyric acid (GABA) receptors, central nervous system activity was suppressed, causing respiratory depression. Additive pharmacological effects should be considered in cases of massive ingestion of multiple drugs.